Pengaruh Disiplin Kerja dan Budaya Organisasi Terhadap Kinerja Karyawan PT BYD Arista Elektrika Pondok Indah - Yusuf Saputra (Jurnal Bisnis Kreatif dan Inovatif, 2025)
This study aims to analyze the influence of Work Discipline and Organizational Culture on Employee Performance at PT. BYD Arista Elektrika Pondok Indah. Employee performance is a key determinant of organizational success, and understanding the internal factors that shape it is essential for effective management. The research employs a quantitative approach, with data collected through questionnaires distributed to 62 respondents representing employees of the company. The data were processed and analyzed using SPSS 27, applying both partial (t-test) and simultaneous (F-test) statistical analyses to examine the significance of the relationships among variables. The results demonstrate that Work Discipline has a positive and significant effect on Employee Performance, emphasizing that adherence to rules, punctuality, and consistent task completion contribute substantially to better performance outcomes. Likewise, Organizational Culture also exerts a positive and significant effect, indicating that shared values, norms, and behavioral patterns within the organization play an important role in shaping employee attitudes and productivity. Furthermore, the F-test findings confirm that both Work Discipline and Organizational Culture, when considered together, significantly influence Employee Performance. The coefficient of determination (R²) is 0.631, meaning that 63.1% of the variance in employee performance can be explained by these two variables, while the remaining 36.9% is attributed to other factors beyond the scope of this study. Specifically, Work Discipline contributes 57.8% and Organizational Culture contributes 51.4% to employee performance. These findings underscore the strategic importance of instilling strong work discipline while simultaneously fostering a supportive and cohesive organizational culture. The practical implication for management is the necessity to design policies and initiatives that not only enforce discipline but also build a positive work environment that motivates employees. Strengthening these aspects is expected to enhance overall productivity, improve organizational outcomes, and create a sustainable competitive advantage for the company.